The Importance of Labor Protection in Production - Bozorov Sanjarbek Dilmurod ogli; Gulomjonov Botirjon Gulomjon ogli; Eshburiyev Ulugbek Ismoil ogli (European Science Publishing, 2023)
The article examines the importance of the organization of Labor security at the enterprise, the issues of their impact on the final results of production activities, conducted a short comparative analysis with foreign experience. Also, the main factors affecting the state of safety of workers in production were considered, and ways to solve the problems that arise in the field of labor protection were proposed.
Keywords: Labor protection, enterprise, safety of workers, economic factor of efficiency, trauma, occupational diseases, safety techniques, environmental factor, psychophysiological condition, protection of employees from harmful and dangerous factors.